NUMERICAL STUDY OF DEPTH FACTORS FOR UNDRAINED LIMIT LOAD OF STRIP FOOTINGS - YAHIA-CHERIF, H.; MABROUKI, A.; MELLAS, M.; BENMEDDOUR, D. (Courrier du Savoir; Vol. 17 (2013): Courrier du Savoir)
Current studies of bearing capacity for shallow foundations tend to rely on the hypothesis of an isolated footing lying on the ground surface. In practice a footing never lies on the ground surface; it is mostly embedded at a depth D below the ground surface. This paper focuses on a numerical study using the finite-difference code Fast Lagrangian Analysis of Continua (FLAC),to evaluate the bearing capacity of embedded strip footings. The effect of the embedment is estimated though a depth factor, defined as a ratio of the bearing capacity of a strip footing at a depth Dto that of a strip footing at the ground surface. The results presented in this paper show that the size and shape of the shear zone and displacement field defining the undrained capacity of shallow foundations under centred vertical loading are dependent on embedment ratio